BLUE ECONOMY: OPPORTUNITIES AND CHALLENGES IN BALOCHSTAN - Dr, Mumtaz Ali; Dr. Hussan Ara Magsi; Farhana Magsi (International Journal of Contemporary Issues in Social Sciences, 2024)
Blue economy is called as “blue growth .”and “maritime economy “.Blue economy refers to promotion of marine resources and to preserve them by protecting the environment .The term basically refer to the sustainable development of the coastal resources in order to boost up economy .The maritime economy is highly neglected by the government .The deep sea port has immense potential to be developed for future prosperity .The aims and objectives of this research paper are To explore new opportunities for sustainable blue economy in Balochistan . To find out the existing challenges confronted to blue economy in Balochistan? 3-To suggest remedies how to promote a sustainable economic growth and development in maritime economy? The qualitative research methodology will be opted in this research work. The data collection took place with help of magazines, books, newspapers and internet websites etc . In the end, there will be viable suggestions that how blue economy can tread upon the sustainable development path by taking governmental support.